GOVERNANCE, DIGITAL FINANCIAL INNOVATIONS, AND GREEN GROWTH: ASSESSING THE IMPACT OF FINTECH ON CARBON NEUTRALITY IN DEVELOPING COUNTRIES - Nageri Kamaldeen (Gusau Journal of Accounting and Finance)
This study examines the interplay between natural resource dependence, fintech development, and fiscal policy in shaping carbon neutrality outcomes in developing economies over the period 2000 to 2023. Utilizing panel data econometric techniques, including fixed effects and dynamic panel models, the analysis reveals that fintech innovation significantly contributes to reducing carbon emissions by enhancing financial inclusion and promoting green investments. Conversely, excessive reliance on natural resources exacerbates environmental degradation, while prudent fiscal policies and institutional quality mitigate these adverse effects. The findings underscore the critical role of digital financial infrastructure and sound governance in advancing sustainable development and environmental stewardship. Policy recommendations advocate for targeted fintech promotion alongside resource management reforms to achieve carbon neutrality goals in emerging markets.